Ectoparasites in Some Wild Birds (Aves) in Turkey - Dik, Bilal; Kandir, Emine Hesna (Progress in Nutrition, 2021)
Study Objectives: Ectoparasites, such as chewing lice, fleas, ticks, mites, etc. can infest domestic and wild birds; and they cause irritation, anorexia, allergic reactions, decrease in animal products, and may transmit some parasitic, rickettsial, and viral diseases to birds. This study was performed to detect ectoparasites on wild birds in the Wildlife Rescue Rehabilitation Training Practise and Research Center of Kocatepe University in Afyon (AKUREM). Methods: In this study, we performed to detect ectoparasites on wild birds between April 2018-2021. In this period, 79 injured or dead wild birds were macroscopically examined for ectoparasites. The ectoparasites collected from the birds were preserved in 70% ethanol, and they were identified to species in the microscopical examination. Results: In a total of 28 ectoparasite species, twenty-one lice, three ticks, two maggots, one hippoboscid fly, and one mite species were detected on the birds. In this study, Upupicola upupae (Schrank, 1803) was detected in Eurasian hoopoe for the first time in Turkey. Conclusion: It was concluded that wildlife rehabilitation centers could be suitable units to provide new findings if applied systematically in ectoparasitary studies.